2018
DOI: 10.1108/jsm-04-2017-0117
|View full text |Cite
|
Sign up to set email alerts
|

Omni-channel service failures and recoveries: refined typologies using Facebook complaints

Abstract: Purpose This paper aims to present two updated typologies of service failures and recoveries in the omni-channel context. These typologies are based on customer complaints and recoveries collected from the corporate Facebook pages of four omni-channel department stores, two operating in Australia and two in the UK. Design/methodology/approach A document review is used of 400 customer complaints and recoveries. Content analysis is used to condense the Facebook data into categories of failures and recoveries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 61 publications
7
94
3
Order By: Relevance
“…Attractive visual merchandising also motivates consumers to stay more time and stimulate purchase [28]. Although the OC evolution is changing consumers' shopping experience, many retailers still fail to deliver a flawless emotional experience [33]. As a result, despite the previous research results, the study on the effect of OC on consumer satisfaction remains to be clarified, and additional research is needed.…”
Section: Oc Consumer and Marketingmentioning
confidence: 99%
“…Attractive visual merchandising also motivates consumers to stay more time and stimulate purchase [28]. Although the OC evolution is changing consumers' shopping experience, many retailers still fail to deliver a flawless emotional experience [33]. As a result, despite the previous research results, the study on the effect of OC on consumer satisfaction remains to be clarified, and additional research is needed.…”
Section: Oc Consumer and Marketingmentioning
confidence: 99%
“…This more holistic picture is important since the literature is abundant with examples of how an integrated approach across channel modes has not performed as expected but interestingly only in relation to how selected aspects of how offline and online platforms are intertwined (e.g., Beck and Rygl, 2015;Ostrom et al, 2015;Rosenmayer et al, 2018;Xiao et al, 2019). Typically, Xiao et al (2019) note more consumers complain about online-tooffline activities (i.e., the use of online platforms to drive in-store sales) than any other area of e-business (p. 214), which is limited in scope but does indicate these two platforms are not fully synchronized in helping to deliver the overall customer experience.…”
Section: Integration Between Social and Technical Chains-of-effectsmentioning
confidence: 99%
“…In practice, BOPS problems arise mostly in the offline pick-up process. Rosenmayer et al ( 2018 )‘s analysis of customer feedback showed that “bricks-and-mortar” shopping problems are most prevalent (24%) among omnichannel service failures, whereas “website design” issues account for only a small proportion (8%). Customers can experience various service problems in the offline channel, where they physically and more intimately interact with the retailer.…”
Section: Introductionmentioning
confidence: 99%